2012
DOI: 10.7205/milmed-d-12-00139
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Prevention of Substance Use Disorders in the Military

Abstract: U.S. military service members have been in active combat for more than 10 years. Research reveals that combat exposure increases the risk of substance use disorders, post-traumatic stress disorder, major depression, and tobacco use. The Services and the field of addiction medicine are working hard to find a common definition for prescription drug misuse, which is a growing concern in both the general U.S. population and the force. Meanwhile, leaders at all levels of Department of Defense are diligently working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…40 It is more difficult to compare disorder-specific AAS prevalence estimates with previous surveys owing to variation in samples and measures, but useful comparisons can be gleaned from 3 recent state-of-the-art reviews on military MDD, 41 PTSD, 42 and SUD. 43 The MDD review found a relatively stable prevalence estimate across 25 US Army surveys, with median prevalence (4.4%) similar to the 4.8% AAS estimate. 41 In comparison, the PTSD review found wide variation in prevalence estimates (2.2%–17.3%) across surveys of Operation Enduring Freedom/Operation Iraqi Freedom/Operation New Dawn servicemembers.…”
Section: Discussionmentioning
confidence: 72%
“…40 It is more difficult to compare disorder-specific AAS prevalence estimates with previous surveys owing to variation in samples and measures, but useful comparisons can be gleaned from 3 recent state-of-the-art reviews on military MDD, 41 PTSD, 42 and SUD. 43 The MDD review found a relatively stable prevalence estimate across 25 US Army surveys, with median prevalence (4.4%) similar to the 4.8% AAS estimate. 41 In comparison, the PTSD review found wide variation in prevalence estimates (2.2%–17.3%) across surveys of Operation Enduring Freedom/Operation Iraqi Freedom/Operation New Dawn servicemembers.…”
Section: Discussionmentioning
confidence: 72%
“…[ 27 28 29 ] Although developmental and early social risk factors are the same as the civilian community, there are also several risk factors associated with military service which are known to increase the risk of substance use disorders, there are cognitive, behavioral, societal, and exposure factors including service-related injuries, experiencing traumatic events in military unit, demands in active duty such as carrying heavy equipment, workplace culture, bad relationship with commanders, service place dissatisfaction, being separated from family members, experiencing boredom, and stress for working in isolated sites. [ 30 31 32 33 ]…”
Section: Resultsmentioning
confidence: 99%
“…Accessing alcohol treatment may initiate involvement of a soldier’s commander and can have negative career ramifications if the soldier fails to comply with the program (10). In addition to the stigma of having a problem and discomfort with help-seeking for substance use problems (38), another barrier to help seeking among Veterans may be their negative beliefs about treatment (12, 39). In light of the high prevalence of substance use, especially alcohol, among active military personnel, it is important that military policies become more conducive to encouraging self-referral, referral from medical professionals, and confidential treatment before alcohol-related behaviors necessitate formal involvement of the soldier’s commander (10).…”
Section: Implications and Conclusionmentioning
confidence: 99%